Speciation rates are correlated with changes in plumage color complexity in the largest family of songbirds. (4th May 2020) - Price‐Waldman, Rosalyn M.; Shultz, Allison J.; Burns, Kevin J.
Abstract: Although evolutionary theory predicts an association between the evolution of elaborate ornamentation and speciation, empirical evidence for links between speciation and ornament evolution has been mixed. In birds, the evolution of increasingly complex and colorful plumage may promote speciation by introducing prezygotic mating barriers. However, overall changes in color complexity, including both increases and decreases, may also promote speciation by altering the sexual signals that mediate reproductive choices. Here, we examine the relationship between complex plumage and speciation rates in the largest family of songbirds, the tanagers (Thraupidae). First, we test whether species with more complex plumage coloration are associated with higher speciation rates and find no correlation. We then test whether rates of male or female plumage color complexity evolution are correlated with speciation rates. We find that elevated rates of plumage complexity evolution are associated with higher speciation rates, regardless of sex and whether species are evolving more complex or less complex ornamentation. These results extend to whole‐plumage color complexity and regions important in signaling (crown and throat) but not nonsignaling regions (back and wingtip). Our results suggest that the extent of change in plumage traits, rather than overall values of plumage complexity, may play a role in speciation.